High-Throughput Screening of Transition-Metal-Atom-Embedded Parallel Tetracyanoethylene 2D Networks as Single-Atom Electrocatalysts for Ammonia Synthesis and Its Underlying Microscopic Mechanisms - Deng, Dan; Song, Bingyi; Li, Cong; Yang, Li-Ming (Journal of physical chemistry. C, 2022)
Electrosynthesis of ammonia under mild conditions has been impeded by the lack of high-performance electrocatalysts. Inspired by the high activity and selectivity of single-atom catalysts (SACs) with maximum atom utilization, we systematically explored a new class of two-dimensional SACs formed by embedding 30 types of transition metals (TMs) in two-dimensional (2D) parallel patterning of tetracyanoethylene (TCNE) networks (labeled as p-TM[TCNE], p means parallel) for the nitrogen reduction reaction (NRR) through the combination of high-throughput screening and density functional theory calculations. Three p-TM[TCNE] (TM = Mo, Nb, Ti) catalysts stand out with high catalytic activity and selectivity. The full reaction path search demonstrates that these three catalysts prefer the distal mechanism, among which p-Mo[TCNE] has the lowest limiting potential of −0.36 V. The origin of high activity might be ascribed to the joint effects from exposed active sites in 2D planar structures, high stability and metallic properties of catalysts, and efficient charge transfer between adsorbed N2 and active sites. Interestingly, the catalytic performance can be correlated well with the magnetic moment of transition metal, which indicates that the magnetic moment could be used as an efficient descriptor for the NRR. This work will shed some light on the rational design of efficient NRR catalysts and stimulate further efforts of both experiment and theory in this field.